Factors Associated with Multidisciplinary Consultations in Patients with Early Stage Breast Cancer. (3rd July 2019) - Quyyumi, Farah F.; Wright, Jason D.; Accordino, Melissa K.; Buono, Donna; Law, Cynthia W.; Hillyer, Grace C.; Neugut, Alfred I.; Hershman, Dawn L.
Abstract: Purpose: Multidisciplinary care (MDC) encourages multiple specialists to formulate a unified treatment plan. We sought to determine the frequency and predictors of MDC and assess the association between MDC and nationally-recognized quality metrics in patients with breast cancer. Methods: We used the surveillance, epidemiology, and end results-medicare dataset to evaluate patients diagnosed with stages I–III breast cancer who underwent breast-conserving surgery between 2002 and 2011 with follow-up to 2012. We defined MDC as a visit claim from a surgeon, radiation oncologist and medical oncologist within 12 months of diagnosis. We used multivariable regression analysis to determine the association between demographic and clinical variables and MDC, and to assess the association between MDC and three nationally-recognized quality indicators (adjuvant hormone therapy for hormone receptor-positive tumors, chemotherapy for hormone receptor-negative cancer, and radiation after lumpectomy). Results: Of the 61, 039 patients in our initial cohort, 53, 849 (88.2%) saw a medical oncologist, 46, 521 (76.2%) saw a radiation oncologist, and 43, 280 (70.9%) were evaluated by all three providers the first year after diagnosis. MDC use was higher in patients with the highest socioeconomic status compared with the lowest [odds ratio (OR) 1.74, 95% CI 1.63–1.86], in patients diagnosed in later years, and those with stage III disease compared to stage I [OR 1.29, 95% CI 1.19–1.41]. Patients older in age (≥80 vs. 65–69 years, OR 0.33, 95% CI 0.31–0.34), patients with more comorbidities, those who lived in a rural setting compared to urban (OR 0.61, 95% CI 0.57–0.64), and unmarried patients (OR 0.79, 95% CI 0.76–0.82) were less likely to see all three providers. In a multivariable analysis, MDC use was associated with increased likelihood of meeting each quality metric. Conclusion: Early stage breast cancer patients were evaluated by a surgeon, radiation oncologist and medical oncologist less than 75% of the time. Enhanced coordination of care and navigation programs may improve the quality of care delivered.